FILSAFAT PENDIDIKAN MODERN JOHN DEWEY: RELEVANSI TERHADAP CARA BELAJAR BAHASA INGGRIS PARIWISATA - Risadi, Md. Yudyantara; Wayan Suastra; Ananta Wikrama Tungga Atmaja; I Nyoman Tika (Sanjiwani: Jurnal Filsafat, 2026)
This research investigated the issue of how the educational philosophy of John Dewey continues to be applicable to the learning of English for Tourism in Indonesia. This study was conducted with the objective of investigating the connections that exist between contextual learning techniques in the field of English for Tourism and Dewey's progressive ideals, which include educational democracy, reflection, and learning by doing.  The purpose of this research was to investigate academic sources that were pertinent in order to discover the practical applications and theoretical ramifications of Dewey's philosophy in vocational English teaching. In order to achieve this objective, the study employed a qualitative literature review methodology. The concept of experience as the central component of meaningful learning that was put forth by Dewey served as the foundation for the theoretical framework.  According to the findings of the study, students who are exposed to experiential, project-based, and reflective learning approaches demonstrate a substantial increase in their ability to communicate effectively, their level of empathy, and their knowledge of social issues.  Furthermore, the implementation of technologies such as virtual reality and digital storytelling contributes to the realization of Deweyan ideals in the digital age.  The consequences made it clear that in order to cultivate professionals who are morally grounded, adaptive, and communicative in the field of tourism, it is necessary to design a form of English for Tourism training that is contextual, reflective, and humanistic.